2014
DOI: 10.1103/physrevb.89.094427
|View full text |Cite
|
Sign up to set email alerts
|

Pinned magnetic moments in exchange bias: Role of the antiferromagnetic bulk spin structure

Abstract: Magneto-optical Kerr effect measurements of epitaxial AFM/FM bilayers and FM/AFM/FM trilayers on Cu 3 Au(001), where "AFM" stands for a Ni 25 Mn 75 antiferromagnetic layer, and "FM" for ferromagnetic layers that are either Ni or Ni/Co with out-of-plane or in-plane easy axis of magnetization, show that trilayers with collinear magnetization directions of both FM layers exhibit always a much lower exchange bias field H eb at a fixed temperature compared to bilayers of the same Ni 25 Mn 75 thickness. At the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…Similar conclusions are drawn from a recent experiment with Ni/NiMn/Ni trilayers which combine in-plane and out-of-plane anisotropies [28]. Fig.…”
Section: Multilayersupporting
confidence: 89%
“…Similar conclusions are drawn from a recent experiment with Ni/NiMn/Ni trilayers which combine in-plane and out-of-plane anisotropies [28]. Fig.…”
Section: Multilayersupporting
confidence: 89%
“…This is due to the fact that the two FM layers with collinear magnetization direction are competing for the pinned uncompensated AF moments, even being magnetized in parallel. During field cooling, the pinned moments separate into two parts, each one providing EB only for one of the FM layers [33]. According to this point of view, in our case, the values of H EB should be the same both for parallel and antiparallel configurations.…”
Section: Resultsmentioning
confidence: 68%
“…Therefore, the suggestion about the existence of magnetic coupling between the FM layers through the AF layer is quite rare [28,29]. In most of the published articles, the authors study the hypothesis of possible interaction or its absence between two exchange bias systems through a common antiferromagnetic spacer [11,13,[21][22][23][30][31][32][33]. Malinowski et al found for FeNi/IrMn/FeNi trilayers that the magnetic coherence of the antiferromagnetic layer at the bottom interface does not extend up to the top, the upper side of the IrMn layer has no chance to get biased from the bottom FeNi layer [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experiments [15,16] and theories [17] have emerged which show that EB is affected by long range interactions in the AF. The spin structure in the bulk of the AF has shown to be crucial determining the magnitude of H EB .…”
mentioning
confidence: 99%